MUCORMYCOSIS (BLACK FUNGUS): INTERPLAY BETWEEN IMMUNOSUPPRESSION, DIABETES MELLITUS, AND GENETIC SUSCEPTIBILITY: A REVIEW - Al-Rhman, Rand Manaf Abd; Mahmood, Marwa Shaker; Turky, Hala Ali (PT. Antis International Publisher, 2025)
Objective: Moulds called mucormycetes are the source of the uncommon but dangerous fungal infection known as mucormycosis, or zygomycosis. Method: Immunocompromised people, such as those with untreated diabetes, haematologic malignancies, and immunological dysregulation brought on by COVID-19, are the main victims. Results: Rapid progression, angioinvasion, tissue necrosis, and a high death rate if left untreated are the disease's hallmarks. Novelty: This study highlights the emerging association of mucormycosis with COVID-19-induced immunological dysregulation, emphasizing its significance in recent patient populations and the urgent need for clinical awareness.